A template model for studying anticancer drug efflux transporter inhibitors in vitro. (8th August 2012) - Sostelly, Alexandre; Payen, Léa; Guitton, Jérôme; Pietro, Attilio Di; Falson, Pierre; Honorat, Mylène; Valdameri, Glaucio; Geze, Annabelle; Boumendjel, Ahcène; Freyer, Gilles; Tod, Michel
Abstract Efflux transporters play an important role in drug absorption and also in multidrug resistance. ABCG2 (BCRP) is an efflux transporter conferring cross‐resistance to mitoxantrone (Mit), irinotecan (CPT11), and its active metabolite SN38. MBLI87, a new ABCG2 inhibitor has proven its efficacy against ABCG2‐mediated efflux in vitro and in vivo. This work aimed at modeling and quantifying the cellular interaction between MBLI87 and different substrates using a mechanistic template model. An in vitro competition experiment study was carried out with HEK293 cells overexpressing ABCG2 exposed to fixed concentrations of substrates (Mit, CPT11, SN38) and to MBLI87 at several concentration levels. A nonlinear mixed‐effects transport inhibition model was developed to fit intracellular drug concentrations. In this model, drugs cross the cell membrane through passive diffusion, active drug efflux is ABCG2 mediated, interaction between substrates and inhibitor occurs within the transporter. The interaction was found to be noncompetitive. The MBLI87 Ki was estimated to 141 nm for Mit, 289 nm for CPT11, and 1160 nm for SN38. The ratio of intrinsic transport clearance divided by diffusion clearance was estimated to 2.5 for Mit, 1.01 for CPT11, and 5.4 for SN38. The maximal increase in the intracellular substrate concentration that is possible to achieve by inhibition of the transporter was estimated to 1.5 for Mit, 0.1 for CPT11, and 4.4 for SN38. This mechanistic template model describes both drug accumulation and cellular transport, and the mixed‐effects approach allows an estimation of intra‐ and interassay variability. This model is of great interest to study cytotoxic cellular pharmacokinetics.